Criminal Law Enforcement Related to the Crime of Child Copulation (Study of Decision Number 429/Pid.Sus/2021/PN Bdg) - Muhammad Gadik Pratama; Anis Widyawati; Dewi Sulistianingsih (Green Publisher Indonesia, 2024)
Indecency includes all acts related to sexual life that violate morality (propriety), including intercourse outside of marriage. The Criminal Code classifies the crime of indecency as a crime against morality. Currently, there is a rise in the crime of indecency, with children often being the victims. Children are part of the younger generation and a potential human resource; therefore, perpetrators of sexual crimes against children must face appropriate punishment. The position of children as the younger generation who will carry forward the noble ideals of the nation requires that their rights and protection be upheld and respected. This research aims to assess the protection provided to child victims of sexual crimes in the city of Pekanbaru, as well as the forms of protection that have been established and implemented in the jurisdiction of the Pekanbaru Police Department (Polresta Pekanbaru). The research was conducted in Pekanbaru, particularly at Polresta Pekanbaru. In terms of data collection techniques, the author used a normative juridical approach, guided by legislation, legal books or literature, and other materials related to the issues and discussions in this thesis. In this context, the important role of parents and the community or the environment is emphasized to provide attention and supervision, ensuring that acts against children as victims of sexual crimes do not occur. Furthermore, in the implementation of legal protection for child victims of sexual crimes, the involved parties must actively and responsibly carry out their duties to ensure the legal protection of child victims of sexual crimes.